Archaea Symbiont of T. cruzi Infection May Explain Heart Failure in Chagas Disease - Higuchi, Maria de Lourdes; Kawakami, Joyce T.; Ikegami, Renata N.; Reis, Marcia M.; Pereira, Jaqueline de Jesus; Ianni, Barbara M.; Buck, Paula; Oliveira, Luanda Mara da Silva; Santos, Marilia H. H.; Hajjar, Ludhmila A.; Bocchi, Edimar A. (Frontiers in Cellular and Infection Microbiology, 2018)
Background: Archaeal genes present in Trypanosoma cruzi may represent symbionts that would explain development of heart failure in 30% of Chagas' disease patients. Extracellular vesicles in peripheral blood, called exosomes (<0.1μm) or microvesicles (>0.1μm), present in larger numbers in heart failure, were analyzed to determine whether they are derived from archaea in heart failure Chagas' disease. Methods: Exosomes and microvesicles in serum supernatant from 3 groups were analyzed: heart failure Chagas' disease (N= 26), asymptomatic indeterminate form (N= 21) and healthy non chagasic control (N= 16). Samples were quantified with transmission electron microscopy, flow cytometer immunolabeled with anti-archaemetzincin-1 antibody (AMZ 1, archaea collagenase) and probe anti-archaeal DNA and zymography to determine AMZ1 (Archaeal metalloproteinase) activity. Results: Indeterminate form patients had higher median numbers of exosomes/case versus heart failure patients (58.5 vs 25.5, P<0.001), higher exosome content of AMZ1 antigens (2.0 vs 0.0; P<0.001), and lower archaeal DNA content (0.2 vs 1.5, P=0.02). A positive correlation between exosomes and AMZ1 content was seen in indeterminate form (r=0.5, P<0.001), but not in heart failure patients (r=0.002, P=0.98). Higher free archaeal DNA (63.0 vs 11.1, P<0.001) in correlation with exosome numbers (r=0.66, P=0.01) was seen in heart failure but not in indeterminate form (r=0.29, P=0.10). Flow cytometer showed higher numbers of AMZ1 microvesicles in indeterminate form (64 vs 36, P=0.02) and higher archaeal DNA microvesicles in heart failure (8.1 vs 0.9, P<0.001). Zymography showed strong % collagenase activity in HF group, mild activity in IF compared to non chagasic healthy group (121 ± 14, 106 ± 13 and 100) (P <0.001). Conclusions: Numerous exosomes, possibly removing and degrading abnormal AMZ1 collagenase, are associated with indeterminate form. Archaeal microvesicles and their exosomes, possibly associated with release of archaeal AMZ1 in heart failure, are future candidates of heart failure biomarkers if confirmed in larger series, and the therapeutic focus in the treatment of Chagas disease.